Aerodynamic damping in cables of overhead transmission lines subjected to wind loads. Issue 4 (August 2018) - Carvalho, Hermes; Correia, José; Jesus, Abílio de; Calçada, Rui
Traditionally, the analysis of cables under the influence of wind is performed using an equivalent static analysis. However, the occurrence of countless accidents in structural systems where cables are involved, even in cases where the project speed limit has not been reached, indicates that the collapse may have been caused by dynamic actions or by underestimated values of wind speed. The aim of this article is to introduce a dynamic analysis methodology for cables under the influence of wind and its forces. The validation procedure proposed is performed through a comparison among the results obtained, results from other researches, and wind tunnel experimental results. In parallel, comparison of the results is obtained in both static and dynamic analysis.